Physiology at a glance / Jeremy P.T. Ward, Roger W.A. Linden - Ward, Jeremy P. T.
Find quick, practical explanations of specialized medical terminology! Davi-Ellen Chabner’s Medical Language Instant Translator, 6th Edition provides a handy reference that’s ideal for everyday use in the classroom and in the health care environment. Access key information on diagnostic tests and procedures, commonly misunderstood medical terms, and interpreting medical reports. Find coverage of the top 100 prescription drugs, medical abbreviations, symbols, and acronyms, and more. Based on Chabner’s The Language of Medicine, this compact resource makes it easier to understand complicated medical terms and communicate more effectively.